Tanzania : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2003)
The staff report summarizes the financial sector issues of Tanzania. It assesses the overall stability and development issues, and provides an overview of the financial system highlighting its soundness and vulnerabilities. It analyzes risk management, regulation and supervision, and the effectiveness of the financial sector. It also summarizes the Reports on the Observance of Standards and Codes on Banking Supervision; and the assessment of Tanzania's adherence to the Basel Core Principles.